Intrinsic Prioritization in Answer Set Programming Based on an Adapted Notion of Tolerance - Marco Wilhelm; Lars-Phillip Spiegel; Gabriele Kern-Isberner (Proceedings of the International Florida Artificial Intelligence Research Society Conference, 2024)
Answer set programming (ASP) is a declarative programming language suited to solve complex combinatorial search problems. Prioritized ASP is the subdiscipline of ASP which aims at prioritizing the models (answer sets) of ASP programs. Common approaches to prioritized ASP require an additional input, sometimes expressed as special literals within the ASP program, that guides the prioritization of the answer sets. In this paper, to the best of our knowledge, we propose the first approach that is able to prioritize answer sets solely based on the original ASP program. For this, we adapt the notion of tolerance from conditional reasoning according to System Z and establish tolerance partitions of ASP programs which can be used for prioritization.